Assessment of regional MR diffusion changes in dementia with Lewy bodies and Alzheimer's disease. (16th December 2013) - O'Donovan, James; Watson, Rosie; Colloby, Sean J.; Blamire, Andrew. M.; O'Brien, John T.
ABSTRACT: Background: Dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) are common forms of dementia, yet diagnosis is often difficult. Diffusion tensor imaging (DTI) is an MR technique used to assess neuronal microstructural integrity that may help develop a better understanding of the differences between the conditions. Methods: We recruited subjects with DLB ( n = 35), AD ( n = 36), and similar aged healthy controls ( n = 35). T1 weighted anatomical and diffusion MR images were acquired at 3 Tesla. Region of interest (ROI) analysis was used to measure fractional anisotropy (FA) and mean diffusivity (MD) in five structures: precuneus, thalamus, pons, midbrain, and amygdala. Where appropriate diffusivity measures (FA, MD) were correlated with selected clinical measures. Results: Compared to controls, DLB subjects were characterized by reduced FA ( p = 0.016) and increased MD ( p = 0.007) in the precuneus. Amygdala diffusivity was positively correlated with UPDRS-III score in DLB ( p = 0.003). In AD, reduced FA in the precuneus was also observed compared to controls ( p = 0.026), and was associated with impaired global cognition (MMSE score) ( p = 0.03). Conclusions: Our findings highlight the potential importance of the precuneus in the pathogenesis of DLB as well as AD. Diffusion tensor MRI may shed new light on the different neurobiological changes underpinning the key clinical features of DLB and AD.